2018
DOI: 10.1167/iovs.18-25466
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Enhances Sphingolipids in Orbital Fibroblasts: Potential Role of Sphingosine-1-Phosphate in Inflammatory T-Cell Migration in Graves' Orbitopathy

Abstract: PURPOSE. Graves' orbitopathy (GO) is an autoimmune orbital disorder associated with Graves' disease caused by thyrotropin receptor autoantibodies. Orbital fibroblasts (OFs) and CD40 play a key role in disease pathogenesis. The bioactive lipid sphingosine-1-phosphate (S1P) has been implicated in promoting adipogenesis, fibrosis, and inflammation in OFs. We investigated the role of CD40 signaling in inducing S1P activity in orbital inflammation. METHODS. OFs and T cells were derived from GO patients and healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 57 publications
(62 reference statements)
0
15
0
2
Order By: Relevance
“…Ceramidases are expressed in epithelial cells and fibroblasts and may be involved in their response through S1P [ 12 , 103 , 113 ]. However, only a limited number of studies have demonstrated the effects of these enzymes in tissue regeneration and healing.…”
Section: Role Of Ceramidases In Tissue Regeneration and Healingmentioning
confidence: 99%
“…Ceramidases are expressed in epithelial cells and fibroblasts and may be involved in their response through S1P [ 12 , 103 , 113 ]. However, only a limited number of studies have demonstrated the effects of these enzymes in tissue regeneration and healing.…”
Section: Role Of Ceramidases In Tissue Regeneration and Healingmentioning
confidence: 99%
“…Besides the proliferative stimulation of the orbital fibroblasts, inflammatory cytokines are released which act to recruit additional immune and inflammatory cells to the orbit [11,12]. The CD40 expression of orbital fibroblasts allows direct interaction with infiltrating T cells with potential additional cytokine release [13]. Since the inflammatory/proliferative processes take place in a bony limited space-the orbit-tissue hypoxia contributes to the pathogenic mechanisms depending on the grade of compression which is caused by the tissue volume changes [14].…”
Section: What Is Graves' Disease?/pathogenic Mechanism Of Graves' Dismentioning
confidence: 99%
“…Another recent in vitro study suggested that sphingosine-1-phosphate (S1P) signaling is involved in orbitopathy [13]. In a follow-up study the immune modulatory potential of S1P receptor antagonist fingolimod (FTY720) was explored in a murine model for Graves' disease [33].…”
Section: Treatment Studies With In Vivo Models Of Go-translation Intomentioning
confidence: 99%
“…Neben der proliferativen Stimulation der Orbitafibroblasten wird auch eine ganze Reihe von inflammatorischen Zytokinen freigesetzt, die zur Infiltration von Immunzellen in die Orbita führen [9,10]. Die CD40-Expression von Orbitafibroblasten erlaubt eine direkte Interaktion mit den infiltrierenden T-Zellen, was die Potenzierung der Zytokin-Freisetzung zur Folge hat [11]. Da sich die entzündliche Gewebevermehrung bei der endokrinen Orbitopathie in einem knöchern begrenzten Raumder Orbitaabspielt, trägt auch eine Gewebehypoxie je nach Ausprägung des Kompressionseffekts zum Entzündungsgeschehen bei [12].…”
Section: Pathogeneseunclassified